Pollinator-syndrome driven changes in the mating systems of two Cape legume species - Nortje, G (Department of Biological Sciences, 2015)
The challenge in answering the question of whether or not plants evolve different mating systems to accommodate their respective pollinators lies in finding a pair of closely related species differing only in pollination syndromes. Furthermore, it has been hypothesized that Non-Flying Mammal Pollination (NFMP) arises from a bird pollinated ancestor as a result of their limited distributions. Liparia splendens subsp. splendens and L. parva are two genetically indistinguishable species that are thought to differ in pollination syndromes and co-occur with similar distributions, densities and have sympatric pollinators. Speculations that closely related sister species L. splendens subsp. splendens and L. parva are bird and nonflying mammal pollination (NFMP) respectively have been confirmed here. Furthermore, mating system divergence in terms of nectar volume and sugar concentration, pollen ovule rations and selfcompatibility has been investigated. There was no difference in nectar volume between the two species investigated, however, nectar concentrations have been found to be significantly higher in L. parva, which is thought to have evolved through selective pressures of pollinator preference. Similarly, pollen ovule ratios in L. parva (22663) are statistically higher than that of L. splendens subsp. splendens (17360), which is predicted to facilitate gene-flow between populations. Both species have been shown to have early-acting self-incompatible (ESI). Similar genetic variation and gene-flow of the two species in question suggest that NFMP is similar to that of bird pollination in its ability to maintain high levels of genetic diversity. The case of Liparia provides a basis to reject the hypothesis of NFMP evolution from a matrix of bird pollinated ancestors due to similar pollinator efficiencies.